Tawaduk Santri In Nusantara Cultural Perspective: A Multi-Discourse Analysis - Khotimah, Khusnul; Lutfitasari, Wevi; Taembo, Maulid; Hipni, Mohammad (el Harakah: Jurnal Budaya Islam, 2024)
The pesantren tradition is a vital aspect of Nusantara culture that shapes students' humility in both religious and cultural practices. This humility (tawaduk) is expressed through distinct attitudes and activities. This study aims to present symbols of students' humility within Nusantara cultural practices and explore the ecological aspects of the unique pesantren culture as portrayed in mass media. This qualitative research utilizes a discourse analysis framework. In mass media discourse, symbols of students' humility are reflected in socio-cultural dimensions through cultural practices such as "cocoghen" rituals, Quranic study sessions ("ngaji kitab"), welcoming the night of Eid al-Adha, seclusion ("khalwat"), and communal meals ("mayoran"). These practices honor Prophet Muhammad, instill noble ethics, foster Islamic brotherhood (ukhuwah islamiyah), encourage surrender to Allah, and promote restraint from worldly desires. Additionally, the pesantren cultural practices serve as environments that preserve local customs, shape students' character, foster brotherhood, offer experiential learning, impart life values, and cultivate self-restraint. The finding of this research provides distinctive insights into the practices of local pesantren traditions, serving as a foundation for the development of the unique cultural heritage of the archipelago. Tradisi pesantren merupakan aspek penting dari budaya Nusantara yang membentuk kerendahan hati (tawaduk) para santri dalam praktik keagamaan dan budaya. Kerendahan hati ini diekspresikan melalui sikap dan aktivitas yang khas. Penelitian ini bertujuan untuk menyajikan simbol-simbol kerendahan hati santri dalam praktik budaya Nusantara serta mengeksplorasi aspek ekologi dalam budaya unik pesantren seperti yang digambarkan dalam media massa. Penelitian kualitatif ini menggunakan kerangka analisis wacana. Dalam wacana media massa, simbol-simbol kerendahan hati santri tercermin dalam dimensi sosial-budaya melalui praktik-praktik budaya seperti ritual "cocoghen", pengajian kitab suci Al-Quran ("ngaji kitab"), menyambut malam Idul Adha, pengasingan diri ("khalwat"), dan makan bersama ("mayoran"). Praktik-praktik ini bertujuan untuk menghormati Nabi Muhammad, menanamkan etika luhur, mempererat ukhuwah Islamiyah, mendorong penyerahan diri kepada Allah, dan menahan diri dari keinginan duniawi. Selain itu, praktik budaya pesantren berfungsi sebagai lingkungan yang melestarikan adat lokal, membentuk karakter santri, mempererat persaudaraan, memberikan pembelajaran melalui pengalaman, menanamkan nilai-nilai kehidupan, dan melatih pengendalian diri. Temuan penelitian ini memberikan wawasan yang khas mengenai praktik tradisi lokal pesantren, yang menjadi dasar pengembangan warisan budaya unik Nusantara.